Measurement of the Bending Strength of Vapor−Liquid−Solid Grown Silicon Nanowires - Hoffmann, Samuel; Utke, Ivo; Moser, Benedikt; Michler, Johann; Christiansen, Silke H.; Schmidt, Volker; Senz, Stephan; Werner, Peter; Gösele, Ulrich; Ballif, Christophe (My University, 2006)
The fracture strength of silicon nanowires grown on a [111] silicon substrate by the vapor−liquid−solid process was measured. The nanowires, with diameters between 100 and 200 nm and a typical length of 2 μm, were subjected to bending tests using an atomic force microscopy setup inside a scanning electron microscope. The average strength calculated from the maximum nanowire deflection before fracture was around 12 GPa, which is 6% of the Young's modulus of silicon along the nanowire direction. This value is close to the theoretical fracture strength, which indicates that surface or volume defects, if present, play only a minor role in fracture initiation.